ANALISIS BENTUK BAHASA BAKU DAN TIDAK BAKU PADA PERCAKAPAN PEDAGANG DAN PEMBELI DI PASAR TRADISIONAL - Cindy Olivia Natasya; Anggreani Hutagalung; Yulia Rizki; Delia Rahmi; Ninis Sekar Ayu; Dina Wahyuni Lubis (STKIP Subang, 2026)
This study aims to analyze the use of standard and non-standard language forms in conversations between sellers and buyers at Pasar Raya MMTC. The research employed a qualitative approach with a descriptive method. Data were collected through direct observation of buying and selling interactions in the market. Observation, note-taking, and documentation techniques were used to record utterances produced by sellers and buyers during transactions. The results indicate that non-standard language is used more frequently than standard language. Non-standard language appears in the form of everyday conversational expressions, the use of certain particles, and a mixture of Indonesian and local languages. This language variety is preferred because it is considered more practical, easier to understand, and suitable for the fast-paced and informal communication that characterizes market interactions. Meanwhile, standard language is used in specific situations, particularly when speakers need to convey information clearly and politely. Factors influencing the use of standard and non-standard language include cultural background, age of the speakers, social environment, communication purposes, and the level of familiarity between sellers and buyers. The findings show that language use in buying and selling interactions is flexible and adapts to the communicative context of the traditional market.